2006
DOI: 10.1016/j.virol.2005.10.034
|View full text |Cite
|
Sign up to set email alerts
|

EBV-encoded dUTPase induces immune dysregulation: Implications for the pathophysiology of EBV-associated disease

Abstract: Epstein-Barr virus (EBV) encodes for several enzymes that are involved in viral DNA replication. There is evidence that some viral proteins, by themselves, can induce immune dysregulation that may contribute to the pathophysiology of the virus infection. In this study, we focused on the EBV-encoded deoxyuridine triphosphate nucleotidohydrolase (dUTPase) and present the first evidence that the dUTPase is able to induce immune dysregulation in vitro as demonstrated by the inhibition of the replication of stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
128
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(136 citation statements)
references
References 43 publications
7
128
1
Order By: Relevance
“…Detailed methods for the purification of the EBV-encoded dUTPase have been previously reported (32,33). All EBV-encoded dUTPase preparations were tested as described previously (32) and were free of detectable levels of LPS, peptidoglycan (SLP-HS), DNA, or RNA.…”
Section: Purification Of the Ebv-encoded Dutpasementioning
confidence: 99%
See 3 more Smart Citations
“…Detailed methods for the purification of the EBV-encoded dUTPase have been previously reported (32,33). All EBV-encoded dUTPase preparations were tested as described previously (32) and were free of detectable levels of LPS, peptidoglycan (SLP-HS), DNA, or RNA.…”
Section: Purification Of the Ebv-encoded Dutpasementioning
confidence: 99%
“…All EBV-encoded dUTPase preparations were tested as described previously (32) and were free of detectable levels of LPS, peptidoglycan (SLP-HS), DNA, or RNA. Protein concentration was determined with a Coomassie Brilliant Blue dye-binding assay (BioRad Laboratories) using BSA as the standard.…”
Section: Purification Of the Ebv-encoded Dutpasementioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies demonstrated that EBV-encoded dUTPase stimulates the expression of proinflammatory cytokines in human PBMCs and HMDM and that the increased cytokine expression was dependent on NF-κB activation (Glaser et al, 2006;Waldman et al, 2008). Recent reports have indicated that TLR2 is also shown to play an important role in immune responses directed against EBV infection.…”
Section: Ebv Infection Of Primary B Cells Causes B Cell Activation Anmentioning
confidence: 99%